Convergence in mycorrhizal fungal communities due to drought, plant competition, parasitism and susceptibility to herbivory: Consequences for fungi and host plants - Gehring, Catherine A.; Mueller, Rebecca C.; Haskins, Kristin E.; Rubow, Tine K.; Whitham, Thomas G. (Frontiers in Microbiology, 2014)
Plants and mycorrhizal fungi influence each other’s abundance, diversity and distribution. How other biotic interactions affect the mycorrhizal symbiosis is less well understood. Likewise, we know little about the effects of climate change on the fungal component of the symbiosis or its function. We synthesized our long-term studies on the influence of mistletoe parasites, insect herbivores, competing trees, and drought on the ectomycorrhizal fungal communities associated with a foundation tree species of the southwestern United States, pinyon pine (Pinus edulis), and described how these changes feed back to affect host plant performance. We found that drought and all three of the biotic interactions studied resulted in similar shifts in ectomycorrhizal fungal community composition, demonstrating a convergence of the community towards dominance by a few closely related fungal taxa. Ectomycorrhizal fungi responded similarly to each of these stressors resulting in a predictable trajectory of community disassembly, consistent with ecological theory. Although we predicted that the fungal communities associated with trees stressed by drought, herbivory, competition, and parasitism would be poor mutualists, we found the opposite pattern in field studies. Our results suggest that climate change and the increased importance of herbivores, competitors and parasites that can be associated with it, may ultimately lead to reductions in ectomycorrhizal fungal diversity, but that the remaining fungal community may be beneficial to host trees under the current climate and the warmer, drier climate predicted for the future.